PERAN TEKHNOLOGI DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI MADRASAH ALIYAH DARUL ULUM BANDA ACEH - Elli, Elli; Nurbayani, Nurbayani; M. Nur, Azhar (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
The integration of technology in Islamic education is crucial for developing critical thinking skills and fostering noble character. This study develops a Student Worksheet (LKPD) based on the Problem-Based Learning (PBL) model to enhance critical thinking skills in the Akidah Akhlak subject at Madrasah Aliyah Darul Ulum Banda Aceh. The research aims to design an effective LKPD, evaluate its impact on learning outcomes, and assess its role in improving critical thinking abilities. Conducted from February 22 to April 12, 2022, the study involved 35 students from Class XI-2 for practicality testing, 25 students from Class XI-4 for effectiveness testing, and two Akidah Akhlak teachers, utilizing the Plomp development model. Data were collected through interviews, curriculum and concept analyses, validation sheets, practicality sheets, and critical thinking tests. The results demonstrate that the LKPD is highly valid (score 4.5), practical (score 4.5), and effective (score 4.67), significantly enhancing students’ critical thinking skills and academic performance. By integrating Islamic values and character education, the LKPD is engaging and relevant to daily life. This research contributes to Islamic education by providing an innovative teaching tool aligned with the 2013 Curriculum, underscoring the role of technology in improving the quality of education in madrasahs. Keyword: Akidah Akhlak; Critical Thinking; Problem-Based Learning; Student Worksheet; Technology in Education